VALIDATION OF THE BASIC PSYCHOLOGICAL NEEDS IN EXERCISE SCALE (BPNES) - Luciane Cristina Arantes da Costa; João Maroco; Lenamar Fiorese Vieira (Journal of Physical Education)
ABSTRACT The study aimed to validate for Portuguese language (Brazilian population) the questionnaire Basic Psychological Needs in Exercise Scale (BPNES) in Physical Education. Attended three translators involved in the translation process, three doctors in Sport Psychology and 403 students. The instrument was the BPNES with 12 items that assessed the basic psychological needs (autonomy, competence and relationship). For analysis, we used the content validity coefficients, kappa, Cronbach's alpha, intraclass correlation and confirmatory factor analysis. The Results showed that the version for the Portuguese language contains appropriate questions for clarity of language and practical relevance (CVC>.81) and presents internal consistency (α=0.83), and satisfactory test-retest reliability (R = 0.87) . Confirmatory factor analysis presented adjustment coefficients (X2/gl=2.10; GFI=0.95; CFI=0.96; TLI=0.95; RMS=0.05). We conclude that the version into Portuguese of BPNES proved to be valid to assessed the constructs of motivation (autonomy, competence and relationships) in the Brazilian educational context.